Analysis of Marketing Strategies and Prices in Increasing Sales - Huriasyahra, H.; Ramli, R.; Hajjad, Mu’fidatul Nurul (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This study aims to determine the marketing strategy for increasing sales at Toko Naya Shop Mamuju. The research employs qualitative methods, with data collected through observation and interviews. The study was conducted at Toko Naya Shop Mamuju, where the shop's owner was the research informant. The interview data were analyzed using SWOT analysis. The results indicate that Toko Naya Shop Mamuju has the following internal factors: four strengths with a total score of 1.05 and four weaknesses with a total score of 1.2. As for external factors, the shop has four opportunities with a total score of 1.03 and four threats with a total score of 0.96. Based on this analysis, Toko Naya Shop Mamuju is positioned in quadrant III, suggesting that the appropriate strategy to adopt is the Turnaround Strategy, a defensive strategy. Although the shop is in a weak position, it has significant opportunities. Therefore, Toko Naya Shop should revise its previous strategy and adopt a new one that aligns with the existing opportunities. The alternative strategies that Toko Naya Shop can implement to increase sales include Increasing business capital to provide fashion products that align with the community's needs, particularly in Mamuju City. Leveraging the development of information technology and using social media as a promotional tool to reach a wider audience and attract potential customers.Increasing the availability of clothing stock to meet the ever-growing fashion demands of the community.Offering wholesale services that reflect current fashion trends.